Análisis de susceptibilidad ante deslizamientos y sus afectaciones a los elementos expuestos en la vía Guanujo-Echeandía sector Piedra Blanca, en el periodo septiembre – diciembre 2024 - Castro Nuñez, Ipatia Rubith (2025)
The objective of this degree work was to determine the susceptibility to landslides and their effects on the exposed elements in the study area, as well as to propose measures that contribute to reduce the associated risks. This is a descriptive research, with a mixed approach using the field method, thus using the ESPE methodology to carry out the landslide susceptibility map and thus fulfill the first specific objective. The determination of the areas susceptible to gradual landslides was carried out using ArcGIS software through the ESPE methodology in which variables such as slope, vegetation cover, precipitation, roads, rivers, are used to obtain the level of susceptibility; very low, low, medium, high, very high, in addition a soil screening was performed to obtain the soil type of the study site and parameters such as fines, gravels and sands to make use of the GEO5 software and demonstrate the result of the slope stability. To obtain the results of the susceptibility level of the exposed elements, an intersection of the landslide susceptibility map with the roads was carried out, obtaining a level between medium and high. Finally, structural and non-structural risk reduction measures were established based on the initial information of the first objective.